Budget management and efficient use of resources in universities - Aguagallo Cando, Robinson Ariel; Barcenes Mendoza, Pomerio Medardo; Ajitimbay Muñoz, Carmita Isabel; Toca Calderón, María Dolores (mktDESCUBRE; Vol 1 No 1 (2020): InnovaEc 2019 Special Edition Congress, 2020)
Summarizing the article, it can be understood that the variations illustrated in the academic budget models and their rules are all noteworthy and depend on the budget model used. Apart from this, there are some common problems that are common in all institutions, even if there are any; A different model is used for the budget. The article shows how the level of centralization or decentralization affects the budget model and how it affects the sources of funding and the budget process for each of the primary budget unit or   departments of the university. As shown in the article, the budget of any university must be determined by the priorities of the institution and the department. As this is one of the main obvious measures of success, this should be the one in which more work should be done. This is also the most important measure for the success of the budget development institution. The article also shows how it is important to identify the general sources of problems in the budget process, the sources of funds, and the sources of expenditures and their types. As mentioned, the process of centralization and decentralization is explained in detail in the article and its relation to the process of budgeting and its relative advantages and disadvantages. Critical decisions regarding the efficient planning of budget resources depend on the significant distance of the definition of the primary budget unit for each of the institution, its level of decentralization, the alignment of desired activities or goals with incentives and identification of the restrictions of the model used, even if it is a hybrid, centralized or decentralized model. All these decisions are important for the planning process of the budget system and the development of the priorities of the institutions and their budgets